The acmeological paradigm of the professional development of a choral conductor within the system of arts education - Vasilyeva, Oksana (Professional Art Education, 2025)
The purpose of the article is to determine the specifics of implementing the acmeological paradigm in the professional development of a choral conductor within the system of music and arts education. The study reveals the acmeological potential of conductor and choral training, outlines the pedagogical conditions that ensure professional growth, and substantiates the interdisciplinary nature of conductor’s education. The article provides a comprehensive characterization of the acmeological approach as a methodological basis for achieving artistic and pedagogical excellence. The main components of choral conductor’s professional mastery are identified as technical precision, emotional expressiveness, and interpretive depth. The study highlights the importance of developing pedagogical intuition, cultural competence, and professional tact, which define the quality of the conductor’s interaction with student choirs and educational collectives. Particular attention is given to the formation of a holistic artistic personality, capable of cultural and educational leadership and scientific initiative. It is argued that the integration of musicology, pedagogy, psychology, and cultural studies ensures effective preparation of conductors for creative, instructional, and community-oriented activity. The research results justify the need to align the content of conductor-choral disciplines with the acmeological principles of lifelong professional and personal development.